Settling the Score: Can CPT-3 Embedded Validity Indicators Distinguish Between Credible and Non-Credible Responders Referred for ADHD and/or SLD?. Issue 1 (January 2023) - Robinson, Anthony; Reed, Christopher; Davis, Katrail; Divers, Ross; Miller, Luke; Erdodi, Laszlo A.; Calamia, Matthew
Objective: The purpose of the present study was to further investigate the clinical utility of individual and composite indicators within the CPT-3 as embedded validity indicators (EVIs) given the discrepant findings of previous investigations. Methods: A total of 201 adults undergoing psychoeducational evaluation for ADHD and/or Specific Learning Disorder (SLD) were divided into credible ( n  = 159) and non-credible ( n  = 42) groups based on five criterion measures. Results: Receiver operating characteristic curves (ROC) revealed that 5/9 individual indicators and 2/4 composite indicators met minimally acceptable classification accuracy of ≥0.70 (AUC = 0.43–0.78). Individual (0.16–0.45) and composite indicators (0.23–0.35) demonstrated low sensitivity when using cutoffs that maintained specificity ≥90%. Conclusion: Given the lack of stability across studies, further research is needed before recommending any specific cutoff be used in clinical practice with individuals seeking psychoeducational assessment.